An investigation of the indigenous ways of knowing about wild food plants (imifino): a case study - Cimi, Phumlani Viwe (Rhodes University, Faculty of Education, Department of Education, 2009)
This study was conducted in Grahamstown in the Eastern Cape, South Africa. It is a qualitative case study located within the interpretive paradigm and was carried out over a period of a year. The theory implicit in the interpretive paradigm is of human beings as interpreters and constructors of a meaningful world. Thus, the focus of this study was on investigating the benefits of indigenous ways of knowing about wild food plants (imifino) in conjunction with hands-on activity-based lessons. This was done with the view to promote a conceptual understanding of nutrition and conservation in the Natural Sciences. The transformation of the school curriculum in South Africa called Curriculum 2005 (C2005) underpinned by the outcomes-based education (OBE) philosophy also triggered this study. The C2005 and OBE emphasise that learners' prior everyday knowledge should be taken into account during the teaching and learning processes. The intention of the curriculum is to promote the idea of grounding knowledge in local contexts, while being sensitive to global imperatives. Although the acquisition of western knowledge has been and still is invaluable to all, on its own, it has been incapable of responding adequately to modern society in the face of massive and intensifying disparities, untrammeled exploitation of resources, and rapid depletion of the earth's natural resources. Essentially, indigenous knowledge systems represent both a heritage and resource that should be protected, promoted, developed and, where appropriate, conserved. It is a resource that should serve the present and succeeding generations as many people's cultural practices still rely on the use of wild plants. Within this context it should be borne in mind that the overexploitation of natural resources threatens not only biodiversity but also local traditional knowledge systems and ultimately cultural heritage; and research has a role to play in this regard. The research process in this study evolved into two main phases. The initial phase involved mobilising Grade 7 learners' prior everyday knowledge on wild food plants (imifino). This led to the second phase of the research project, which was aimed at developing concepts through three hands-on activity-based lessons. I invited a community member to give a lesson on what imifino is and how to collect and prepare it, with the belief that the involvement of parents and community members in learners' education can help bridge the gap between everyday life and school science. It is for these reasons that I believe that the constructive perspective can provide an appropriate methodological framework, conceptual structure and terminology for analysis of teaching and learning activities on the use of wild food plants in this study. The data generation techniques used in this study were questionnaires, observations and interviews (semi structured and focus group). A wide range of data generation techniques were employed to crystallise and validate the data generated using triangulation. The results from the analysed data revealed that consideration of indigenous ways of knowing in conjuction with hands-on practical activities enhanced interaction and learning among the learners. Also, linking of scientific knowledge to learners' everyday lives was useful in fostering meaning-making and conceptual development.
Keywords: Wild plants, Edible -- South Africa -- Eastern Cape -- Case studies; Endemic plants -- South Africa -- Eastern Cape -- Case studies; Ethnoscience -- Study and teaching -- South Africa -- Eastern Cape; Science -- Study and teaching -- South Africa -- Eastern Cape; Curriculum change -- South Africa -- Eastern Cape; Competency-based education -- South Africa -- Eastern Cape; Conservation of natural resources -- South Africa -- Eastern Cape